“Academia da Saúde” program: mapping evidence from the largest health promotion community program in Brazil - Diego Augusto Santos Silva; Tiago Rodrigues de Lima; Letícia Gonçalves (Frontiers in Public Health, 2023)
The aim of this scoping review was to map the literature related to the “Academia da Saúde” Program, including the objective and rationale of the studies, activities carried out in the program’s centers, as well as the actors involved in these actions. The search for evidence was conducted in the MEDLINE, LILACS, Web of Science, Scopus, COCHRANE, and SciELO databases. Additional evidence was investigated in the Catalog of Theses and Dissertations of the Coordination of Improvement of Higher Education Personnel (CAPES-Brazil) and in the Brazilian Digital Library of Theses and Dissertations, in addition to manual searches in the references of the studies/documents. Out of 642 initial records, the information synthesis was composed of 74 studies/documents (n = 54; 73.0% scientific articles, n = 48; 64.9% with cross-sectional design, n = 45; 60.8% quantitative analysis). Nutrition (n = 24; 32.2%) and evaluation of the Program (n = 27; 36.5%) were the main themes analyzed. Regarding the participant/object analyzed in each study, users (n = 39; 52.6%) were the main actors investigated. Future studies should consider investigating the effectiveness of the actions developed in the program centers, especially physical activity and healthy eating practices.